Neck circumference cut-off points for detecting overweight and obesity among school children in Northern Cyprus - Turkay, Ezgi; Kabaran, Seray (Bmc, 2022)
Background Neck circumference is one of the anthropometric parameters that is widely used in practical applications, clinical and epidemiological studies in children. It is aimed to determine the neck circumference cut-off points and to use them in the detection of overweight and obesity in children living in Northern Cyprus. Subjects This cross-sectional study was conducted between October 2019 and January 2020, and covered a sample of 692 children (367 girls and 325 boys) aged 6-10 years attending primary schools in the Northern Cyprus. Methods Body weight, height, neck circumference, waist circumference, subscapular and triceps skinfold tickness were measured. BF% was calculated with Slaughter equations. World Health Organization BMI cut-off points for age and gender percentiles were used to categorize obesity. BMI, WHtR, NC, body fat were calculated. The Pearson Correlation co-efficient between NC and the other anhtropometric measurements were calculated. Receiver operating characteristics analysis, sensitivity, specificity, PV + ve PV- was used to determine the optimal NC cut-off points for identifying children with overweight and obesity. Results NC was a statistically significant positive and strong relationship with body weight, BMI, waist circumference and hip circumference (p < 0,005). NC cut-off values to define overweight and obesity were calculated as 26,9 cm in girls (AUC: 0,851, 95% CI: 0,811-0,891, sensitivity 70,50%, specificity 84,65%) and 27,9 cm in boys (AUC: 0,847, 95% CI: 0,805-0,888, sensitivity 76,4%, specificity 79,3%). The ROC curves accurately define overweight and obesity of the whole cohort regardless of age for both sexes of children. Conclusions The cut-off points for neck circumference were found to be 27,9 cm for boys and 26,9 cm for girls in determining overweight and obesity in children aged 6-10 years. The NC cut-off points obtained in this study can be used to define overweight and obesity in children in epidemiological studies. It is considered to shed light on studies that will examine the relationship between neck circumference and diseases with more people in future studies.
Keywords: Neck circumference; Cut-off points; School children; Overweight and obesity